Pengaruh Model Pembelajaran Generatif terhadap Kemampuan Pemecahan Masalah Matematika - Dewi Sulistiawati (Universitas Indraprasta PGRI, 2017)
The benefit of this research is to analyze the Impacts of Generative Learning Model on Mathematics problem Solving Skills. The method used in this research is experiment through t test. To collect the data about generative learning model, the writer used her idea, scientific books, scientific journals, internet and others documents. The research was conducted on the students of class VII H and VII G at Public SMP in west Cikarang. The sample is about 60 students. Before using generative learning model’s instruments, they was validated and past reability test. After that the writer done normality test through chi kuadrat test and homogeneity test through fisher test. Based on the research, t test ? t table (2.21 ? 1.697). it means there are significant impacts of Generative learning model on Mathematics problem solving. It can be concluded that there are significant impacts of Generative Learning Model on Mathematics problem Solving Skills.